Elemental profiling and identification of eco-toxic elements in agricultural soil by laser-induced breakdown spectroscopy - Haider, A F M Yusuf; Kabir, Firoza; Ullah, M. Hedayet; Khan, Z.H.; Abedin, Kazi M. (© 2013 Science and Education Publishing, 2017)
This article was published in the Journal Applied Ecology and Environmental Sciences [© 2013 Science and Education Publishing] and the definite version is available at: 10.12691/aees-1-4-1